Say no to the duke - James, Eloisa (James, Eloisa. Wildes of Lindow Castle., 2019)
Lady Betsy Wilde<U+2019>s first season was triumphant by any measure, and a duke has proposed<U+2014>but before marriage, she longs for one last adventure. No gentleman would agree to her scandalous plan<U+2014>but Lord Jeremy Roden is no gentleman. He offers a wager. If she wins a billiards game, he<U+2019>ll provide the breeches. If he wins<U+2026>she is his, for one wild night. But what happens when Jeremy realizes that one night will never be enough? In the most important battle of his life, he<U+2019>ll have to convince Betsy to say no to the duke.